Management of halitosis secondary to periodontal disease: report of four cases - E. B. Dosumu (Nigerian Dental Association, 2009)
Halitosis is an offensive odour emanating from the oral cavity and it is a common clinical condition. The purpose of this study is to emphasize the importance of the correct diagnosis of the type of halitosis in order to achieve a successful management. The four cases reported in this study revealed that a cause of the halitosis can be found most of the time following thorough examination. Elimination of the cause or source of the mal-odour eventually eliminates the halitosis. Dental practitioners should therefore be cautious in making a diagnosis of pseudo-halitosis and halitophobia which are very rare conditions and they should patients should be referred for expert management.